The Narrative Affordances and Limitations of Internal Focalization for Creating Suspense and Surprise in Persian Detective Novels, A Case Study: Esmail Fassih’s the Falcon and the Owls - Reza Nekoei; Kavoos Hassanli; Saeed Hessampour (Iranian Journal of Applied Language Studies, 2022)
Various types of focalization are important elements in creating suspense and surprise. This study finds use of narrative discourse analysis in order to discover the narrative affordances and limitations of internal focalization for creating suspense and surprise in Persian detective novels, specifically, Esmail Fassih’s The Falcon and the Owls. Duality (the existence of two temporal sets in the structure of the narrative), raising implicit questions in the first and other scenes of the novel, flashback, flashforward, different types of internal and external conflicts, spatial limitation of the focalizer and the suspense after the surprise are some of the affordances and limitations of the internal focalizer in creating suspense and surprise. In The Falcon and the Owls, the most significant strengths of the internal focalizer are the extensive attention given to narrative affordances such as raising implicit questions in the first and other scenes of the novel as well as going back and forth in time; while its weaknesses include giving insufficient attention to the tactic of multiple internal focalization, paying unnecessary attention to unimportant omissions and omitting important events.